Immunotherapy in translational cancer research - Cooper, Laurence J. N.; Mittendorf, Elizabeth A.; Moyes, Judy, 1953-; Prabhakaran, Sabitha (Translational oncology (Series), 2018)
"Immunotherapy in Translational Cancer Research is a volume in Translational Oncology, an exciting book series that focuses on translational cancer research. Immunotherapy has become a key aspect in the treatment of a wide variety of cancers, and this book is specifically designed for physicians, clinical fellows, medical students, graduate students, scientists, pharmaceutical executives, public health and public policy government leaders and community oncologists. Each chapter is consistently organized and features three essential themes: Development of the immunotherapy; Hurdles that were overcome to scale up and undertake clinical trials; and Clinical experience and application of research. Concepts, examples and alternative strategies to achieve individualized targeted therapy are presented, with thorough consideration of the relevant history, current state and future directions of emerging cancer-fighting therapies, drug development, clinical trials, and governmental resources and regulatory issues."--Provided by publisher.